2008
DOI: 10.1016/j.bbamcr.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin–proteasome system mediates heme oxygenase-1 degradation through endoplasmic reticulum-associated degradation pathway

Abstract: The present study investigated the cellular mechanism underlying the degradation of heme oxygenase-1 (HO-1), an endoplasmic reticulum (ER)-anchored protein. The turnover of HO-1 induced in vascular smooth muscle cells (VSMCs) was significantly attenuated by proteasome inhibitors, suggesting the involvement of a proteasome-mediated pathway. High molecular weight ubiquitin conjugates were co-immunoprecipitated with HO-1 from VSMCs after proteasome inhibition, and HO-1 ubiquitination was confirmed in HEK293 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…However, RNAi-mediated depletion of Ufd1 in mammalian cells has yielded opposite results. While some studies reported impaired ERAD in Ufd1-depleted cells (6,7), others showed accelerated degradation of the classical ERAD substrates, such as cholera toxin and T-cell receptors (8,9). Although these seemingly contradictory observations might stem from the use of distinct cellular systems, they point to greater complexity in the regulation and function of Ufd1 that impinge on the ER stress response.…”
mentioning
confidence: 83%
“…However, RNAi-mediated depletion of Ufd1 in mammalian cells has yielded opposite results. While some studies reported impaired ERAD in Ufd1-depleted cells (6,7), others showed accelerated degradation of the classical ERAD substrates, such as cholera toxin and T-cell receptors (8,9). Although these seemingly contradictory observations might stem from the use of distinct cellular systems, they point to greater complexity in the regulation and function of Ufd1 that impinge on the ER stress response.…”
mentioning
confidence: 83%
“…The knockdown of both miR-217 and miR-377 increases HO-1 protein expression, while the overexpression of the same miRNAs leads to attenuation of protein expression [40]. Recently, Lin et al show that HO-1 is subjected to posttranslational regulation by the ubiquitin-proteasome system through an endoplasmic reticulum-associated degradation pathway [41]. Proteasome inhibition significantly decreased HO-1 protein degradation.…”
Section: Regulation Of Ho-1 Gene Expressionmentioning
confidence: 99%
“…Therefore, induction of HO-1 has been thought to produce protective effects against a variety of cellular stresses [20]. The expression of HO-1 is regulated mainly at the transcriptional level [21], although a mechanism of HO-1 degradation through the endoplasmic reticulum-associated degradation pathway has been reported [22]. The promoter sequences of HO-1 contain two enhancer regions (E1 and E2) providing binding motifs for a variety of transcription factors, such as activator protein (AP)-1, cAMP-responsive element binding protein (CREB), NF-κB or Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) [23].…”
Section: Introductionmentioning
confidence: 99%